2012
DOI: 10.1111/j.1365-2702.2012.04128.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual functioning in nursing home residents: information in client records

Abstract: In this study, one-third of nursing homes residents have visual problems, needing examination by an ophthalmologist. Problems with visual functioning should be assessed and captured in client records. Awareness of residents' visual functioning is a prerequisite for adapting basic daily care to the residents' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Four different nursing home organizations (with seven nursing home buildings) in the central region of the Netherlands participated in both previous studies (Sinoo, Van Hoof, & Kort, 2011;Sinoo, Kort, & Duijnstee, 2012). These organizations were motivated to improve the awareness of adequate eye care among their caregivers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four different nursing home organizations (with seven nursing home buildings) in the central region of the Netherlands participated in both previous studies (Sinoo, Van Hoof, & Kort, 2011;Sinoo, Kort, & Duijnstee, 2012). These organizations were motivated to improve the awareness of adequate eye care among their caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…In this first study no information about client records was given. The second study (Sinoo, Kort, & Duijnstee, 2012) addressed the recording of general eye care information in client records in the seven nursing homes. The findings of this second study showed that a significant proportion of client records showed no recorded information on visual functioning (the use of spectacles; normal vision, low vision or blindness).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,[12][13][14] The importance of awareness of nursing home residents' visual functioning has been addressed by former studies. [6,[13][14][15][16] A supporting tool might raise professional caregivers' awareness of these environmental factors, indicated as (building) physical aspects in Figure 1. In a pilot study, [17] the content and layout of the Environmental Observation tool for the Visually Impaired (EOVI-63) was determined by use of a literature search and open observations in seven nursing homes.The tool was developed because previous studies howed that nursing homes had poor light conditions and because of professional caregivers' lack of awareness of these light conditions and their effect on the residents.…”
Section: Introductionmentioning
confidence: 99%